Correlation between perioperative dexmedetomidine administration and postoperative acute kidney injury in hypertensive patients undergoing non-cardiac surgery - Li, Bo; Chen, Minghua; Zeng, Youjie; Luo, Siwan (Frontiers in Pharmacology, 2023)
Background: Previous studies have suggested that dexmedetomidine may have a protective effect on renal function. However, it is currently unclear whether perioperative dexmedetomidine administration is associated with postoperative acute kidney injury (AKI) incidence risk in hypertensive patients undergoing non-cardiac surgery. Methods: This investigation was a retrospective cohort study. Hypertensive patients undergoing non-cardiac surgery in Third Xiangya Hospital of Central South University from June 2018 to December 2019 were included. The relevant data were extracted through electronic cases. The univariable analysis identified demographic, preoperative laboratory, and intraoperative factors associated with acute kidney injury. Multivariable stepwise logistic regression was used to assess the association between perioperative dexmedetomidine administration and postoperative acute kidney injury after adjusting for interference factors. In addition, we further performed sensitivity analyses in four subgroups to further validate the robustness of the results. Results: A total of 5769 patients were included in this study, with a 7.66% incidence of postoperative acute kidney injury. The incidence of postoperative acute kidney injury was lower in the dexmedetomidine-administered group than in the control group (4.12% vs. 8.06%, p < 0.001). In the multivariable stepwise logistic regression analysis, perioperative dexmedetomidine administration significantly reduced the risk of postoperative acute kidney injury after adjusting for interference factors [odds ratio (OR) = 0.56, 95% confidence interval (CI): 0.36–0.87, p = 0.010]. In addition, sensitivity analysis in four subgroups indicated parallel findings: i) eGRF <90 mL/min·1.73/m2 subgroup (OR = 0.40, 95% CI: 0.19–0.84, p = 0.016), ii) intraoperative blood loss <1000 mL subgroup (OR = 0.58, 95% CI: 0.36–0.94, p = 0.025), iii) non-diabetes subgroup (OR = 0.51, 95% CI: 0.29–0.89, p = 0.018), and iv) older subgroup (OR = 0.55, 95% CI: 0.32–0.93, p = 0.027). Conclusion: In conclusion, our study suggests that perioperative dexmedetomidine administration is associated with lower risk and less severity of postoperative acute kidney injury in hypertensive individuals undergoing non-cardiac surgery. Therefore, future large-scale RCT studies are necessary to validate this benefit.